Decentering comparative analysis in a globalizing world - Giraud, Olivier; Lallement, Michel (International comparative social studies, 2021)
"Decentering Comparative Analysis in a Globalizing World aims to go beyond the traditional criticism in comparative analysis. It wants to shed new light on the question of comparing as a form of categorizing. In this perspective, three relevant dimensions to question the naturalized categories of comparison are mobilized: ethnocentrism, the nation, and academic disciplines. Based on original empirical work, the volume proposes to use comparative categories by mixing and shifting the analytical perspectives. It brings together contributions that come to terms with the historicity of the comparative method in the social sciences. It eventually deals with the key issue of comparability of various cases, in the enlarged context of a globalizing world"--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Empirische Sozialforschung; Kulturvergleich; Globalisierung